Effects of Exposure Time and Temperature on Screw Driving Torques in Heat-Treated Anatolian Black Pine and Sessile Oak Wood - Karamanoglu, Mehmet; Tor, Önder (Faculty of Forestry, University of Zagreb, 2022)
This study aimed to investigate the characteristics of screw driving torques in heat-treated Anatolian black pine and sessile oak wood. The wood samples were subjected to heat under atmospheric pressure at three different temperatures (130, 180 and 230 °C) and two different exposure time levels (2 and 8 h). Screw driving torques of seating and stripping torque (SET and STT) was performed on all samples. The process of screw driving had two main torques, one of which was the seating torque defined as the torque required to clamp parts and the other one was the stripping torque defined as the maximum torque right before the screw strips in the material and the torque drops suddenly because of the formed screw threads being stripped in wood material. Results show that, in both wood species, the SET and STT values decreased due to the increase in heat treatment temperature and exposure time compared to the control groups.
Keywords: pilot-rupa; vijak; pilot hole; seating torque; Forestry; screw; zakretni moment zatezanja; SD1-669.5; heat-treated wood; toplinski obrađeno drvo